Noninvasive strategies in COVID-19: epistemology, randomised trials, guidelines, physiology. Issue 2 (18th February 2021) - Tobin, Martin J.; Jubran, Amal; Laghi, Franco
Coronavirus disease 2019 (COVID-19) is producing seismic changes in society at large and the action of doctors is receiving greater attention from the public than ever in our lifetime. The medical care provided to millions of patients suffering from a single disease constitutes an experiment of nature of extraordinary proportions. The release of voluminous data into medical journals provides the spur to meditate on long-held assumptions about the way we interpret clinical research. Two recent ERJ articles demonstrate dramatic benefit with CPAP in COVID-19 patients, highlighting problems with the landmark trial of CPAP (and related guidelines) and illustrating the danger of believing that trials capture the truth of clinical practice https://bit.ly/3pVp78e